Born to run 2 : the ultimate training guide - McDougall, Christopher, 1962-; Orton, Eric (Running coach) (Alfred A. Knopf, 2022)
An illustrated, practical, and holistic guide for every kind of runner, with tips on nutrition, training, shoe recommendations, and suggestions for finding a running community.